Hubungan Motivasi dan Kemandirian Belajar Mahasiswa Calon Guru Sekolah Dasar - Rahmatih, Aisa Nikmah; Fauzi, Asri; Ermiana, Ida (Wahana Sekolah Dasar, 2020)
This study aims to find out how the relationship between learning motivation and learning independence of prospective elementary school teacher students. Samples used as respondents in this study were 52 PGSD students at Mataram University. Data collection instruments using a questionnaire of motivation and independence of learning questionnaire consisting of 30 items statement. The form of the questionnaire used in this study was a Likert scale questionnaire with 4 alternative choices of answers. The data analysis technique used is the Pearson Product Moment correlation test. Before the correlation test is performed, it must first meet the classical assumption test requirements, namely the normality test and the linearity test. The normality test results obtained sig. (0.927) more than 0.05 then the data is normally distributed, then the linearity test results obtained sig. (0.603) more than 0.05 then there is a linear relationship between the two variables. The results of the Pearson Product Moment correlation test showed the value of sig. (2 tailed) 0,000 less than 0.05 and Rvalue (0.849) more than Rtable (0.279) which means that there is a significant relationship between motivation and student learning independence, and the resulting degree of relationship is the relationship motivation with student learning independence correlates perfectly.Â Penelitian ini bertujuan untuk mengetahui bagaimana hubungan antara motivasi belajar dengan kemandirian belajar mahasiswa calon guru sekolah dasar. Sampel yang dijadikan responden pada penelitian ini sebanyak 52 mahasiswa PGSD Universitas Mataram. Instrumen pengumpulan data menggunakan angket motivasi dan angket kemandirian belajar yang terdiri dari 30 item pernyataan. Bentuk angket yang digunakan dalam penelitian ini adalah angket skala likert dengan 4 pilihan alternatif jawaban. Teknik analisis data yang digunakan adalah uji korelasi Pearson Product Moment. Sebelum dilakukan uji korelasi maka terlebih dahulu memenuhi syarat uji asumsi klasik yaitu uji normalitas dan uji linearitas. Hasil uji normalitas didapatkan sig. (0,927) lebih dari 0,05 maka data berdistribusi normal, kemudian hasil uji linearitas didapatkan sig. (0,603) lebih dari 0,05 maka ada hubungan yang linear antara kedua variabel. Hasil analisis uji korelasi Pearson Product Moment menunjukkan nilai sig.(2 tailed) 0,000 kurang dari 0,05 dan Rhitung (0,849) lebih dari Rtabel (0,279) yang artinya ada hubungan yang signifikan antara motivasi dengan kemandirian belajar mahasiswa, dan derajat hubungan yang dihasilkan yaitu hubungan motivasi dengan kemandirian belajar mahasiswa berkorelasi sempurna.